Organic geochemical assessment of black shales: case study of Oued Soura, Tamtret region, Algeria - Kadou, Abdelghani; Rebhi, Boudjema (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: Black shales are increasingly recognized as signif- icant unconventional hydrocarbon sources due to their organic richness and potential for oil and gas generation. However, their complex geo- chemical nature, especially in underexplored regions such as Tamtert in southwestern Algeria, poses challenges to accurate evaluation. This study aims to assess the hydrocarbon potential of black shales from the Djebel-Zereg area using advanced organic geochemical methods.Methods: Five black shale samples were collected from Djebel-Zereg, Tamtert region. Total Organic Carbon (TOC) content was determined, and Rock-Eval 6 pyrolysis and elemental analysis were conducted. Pa- rameters measured included TOC, S1, S2, Tmax, Hydrogen Index (HI), Oxygen Index (OI), and vitrinite reflectance (Ro), providing data on or- ganic matter type, thermal maturity, and hydrocarbon generative capac- ity.Results: TOC values ranged from 0.51 to 2 wt.% with an average of 1.33 wt.%, indicating acceptable to very good source rock quality. S2 values ranged from 0.45 to 4 mg HC/g rock, and the average Production Index (PI) was 2.23. HI values (51–233 mg HC/g TOC), along with OI and Tmax, indicated the presence of type II and III kerogen, suggesting potential for both oil and gas generation. Tmax values (435–465°C, av- erage 447°C) and vitrinite reflectance (0.68%–1.19%) confirmed thermal maturity. A positive correlation between TOC and S1 values supported the presence of indigenous hydrocarbons.Conclusion: The integrated geochemical approach confirms that the Djebel-Zereg black shales are thermally mature, organic-rich rocks with promising oil shale potential. These findings support further explo- ration and development of unconventional hydrocarbon resources in the Tamtert region.
Keywords: black shale; Djebel-Zereg; elemental analysis; hydrocarbon potential; organic matter; Rock-Eval pyrolysis; source rock evaluation; total organic carbon